The Influence Of The Five "C's" Of Credit On The Process Of Providing credit (Study At PT Bank Tabungan Negara Tbk. Kajoalalido Makassar Branch Office) - Aliftha Pebruanti Achmad; prof. Dr. H. Syamsu Alam, S.E. M.Si.CIPM; Dr. Mursalim Nohong, S.E.M.Si.CRA.CRP.CWM (International Journal of Business and Quality Research, 2023)
This study aims to analyze the influence of the five C's of credit on the credit providing process at Bank Tabungan Negara (BTN) Kajoalalido Makassar. The variables used in this research are character, capacity, capital, collateral and economic conditions as independent variables and the credit providing process as the dependent variable. This research uses a quantitative approach and data analysis methods using multiple linear regression analysis with the help of the SPSS program. The results of data analysis in this research show that the variables character, capacity, capital, and collateral do not have a significant effect on the credit providing process. Meanwhile, the condition of economic variable has a positive and significant effect on the credit providing process.